(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
Monitoring and analyzing the effectiveness of teachers in preschool educational institutions is an important component of ensuring high-quality education for early childhood. This article examines modern opportunities and strategies for assessing and improving the performance of educators in preschool educational institutions. By exploring innovative monitoring methods, data analysis tools, and the foundations of performance evaluation, this article aims to provide insights into improving teaching practices, promoting professional development, and optimizing educational outcomes for early childhood education.